Targeted treatment of acute myeloid leukemia in older adults: role of gemtuzumab ozogamicin - Hien K Duong (Dove Medical Press, 2009)
Hien K Duong, Mikkael A SekeresCleveland Clinic Taussig Cancer Institute, Cleveland, Ohio USAAbstract: As the overall prognosis and treatment response rate to standard chemotherapy for acute myeloid leukemia (AML) remains poor in the older adult population, there is a need for more effective therapeutic agents with lower toxicity profiles that can be offered to these patients. Gemtuzumab ozogamicin (GO) is an anti-CD33 monoclonal antibody that was approved by the US Food and Drug Administration for use as monotherapy in patients 60 years of age and older with relapsed AML. GO consists of a humanized anti-CD33 antibody (hP67.6) which is linked to N-acetyl-γ calicheamicin 1,2-dimethyl hydrazine dichloride. Once the antibody attaches to the surface antigen, it is rapidly internalized. Calicheamicin, a potent enediyne, is subsequently released and acts as a cytotoxic anti-tumor agent. In this population, GO has an acceptable toxicity and yields response rates approaching 30%. The efficacy of GO as monotherapy and in combination therapy for treatment of both de novo and relapsed AML continues to be investigated.Keywords: acute myeloid leukemia therapy, older adults, gemtuzumab ozogamicin